Successful Treatment of Aortic Endocarditis by Achromobacter xylosoxidans with Cefiderocol Combination Therapy in a Non-Hodgkin Lymphoma Patient: Case Report and Literature Review - Gianfranco La Bella; Francesco Salvato; Graziano Antonio Minafra; Irene Francesca Bottalico; Tiziana Rollo; Lucia Barbera; Samantha De Tullio; Gaetano Corso; Sergio Lo Caputo; Rosella De Nittis; Fabio Arena (MDPI AG, 2022)
Achromobacter xylosoxidans is a Gram-negative aerobic opportunistic bacterium, belonging to the order of Burkholderiales, that can cause infections of virtually all body districts in patients with underlying diseases. However, A. xylosoxidans has rarely been associated with infective endocarditis. The treatment of A. xylosoxidans infections is complicated by both intrinsic and acquired resistance. Here we report on a case of aortic endocarditis by A. xylosoxidans in a Non-Hodgkin lymphoma patient treated with a combination of cefiderocol and other antibiotics, and summarize the available literature.